Analisis Perbandingan Filter Median dan Gaussian dalam Mengurangi Noise pada Citra Digital - Puji Sri Alhirani; Lailan Sofinah Harahap; Rani Chantika (Lembaga Pengembangan Kinerja Dosen, 2025)
. Digital image processing is one of the important aspects in the world of technology, especially in improving image quality from noise interference. This study aims to analyze and compare the performance of the Median Filter and Gaussian Filter in reducing salt & pepper noise in digital images. The research process was carried out using the Python programming language and the OpenCV and NumPy libraries. The initial image was randomly noised, then processed using both types of filters. The results obtained were evaluated visually and quantitatively using the PSNR (Peak Signal-to-Noise Ratio) and MSE (Mean Squared Error) metrics. Based on the experimental results, the Median Filter was able to produce cleaner images and maintain image details compared to the Gaussian Filter. These results indicate that the Median Filter has advantages in handling salt & pepper noise. This study is expected to be a reference in selecting the right filtering method to improve the quality of digital images.